Tabby McTat - Donaldson, Julia; Scheffler, Axel. (London : Scholastic, 2009)
Me, you and the old guitar, How perfectly happy we are. MEEE-EW and the old guitar. How PURRRR-fectly happy we are.
Keywords: Cats -- Fiction; Singers -- Fiction